Helicobacter pylori Seropositivity in Children in Duhok City, Iraq - Yahya, Nizar B. (Science Journal of University of Zakho, 2018)
Introduction: Helicobacter pylori(H. pylori) is a gram negative bacteria that causes gastritis and peptic ulcer disease (PUD). It is widely accepted that the infection may occur early in life and may persist for decades before causing diseases. The aim of this paper was to determine the prevalence of H. pyloriseropositivity in pediatric age group and to examine the associated risk factors. Patients and methods: Blood samples were collected from 100 subjects attending Hevi Pediatric Teaching Hospital over a period of 6 months and IgG positivity was determined. A questionnaire sheet was prepared and used for each study subject. Data were collected by a face-to-face interview.Results: It was found that 28/100 (28%) of the recruited sample was positive for H. pyloriseropositivity. A significant association was found between the number of siblings and H. pyloripositivity (P=0.01, OR=1.3). No significant relationships were found between other factors and H. pyloripositivity. Conclusions: The prevalence of H. pyloriinfection was less than that reported in the city previously and less than that reported in neighboring countries. A significant positive association was found between number siblings and H. pyloriinfection rate. Further studies are needed recruiting larger sample size to explore H. pyloriprevalence and its associated risk factors.